2020
DOI: 10.1080/14427591.2020.1758200
|View full text |Cite
|
Sign up to set email alerts
|

A critical occupational perspective on user engagement of older adults in an assisted living facility in technology research over three years

Abstract: Digital assistive technology has potential for supporting older adults who depend upon community healthcare services. To boost the efficiency of those services, technological devices are often installed for care recipients as part of governed practice. However, the varying adoption of technology risks widening the digital divide. In response, the Assisted Living project engaged older adults in co-creating knowledge about users' needs, to guide the development of technological solutions designed to support ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The housekeeper also contacted the researchers when needed. These findings are presented in other papers [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The housekeeper also contacted the researchers when needed. These findings are presented in other papers [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 86%
“…One report highlighted that one of the motivations for the residents was to be of benefit for others, exemplified by one group leader as follows: ‘They know they are helping us for future generations of older adults, which I believe is their own motivation.’ (DC2). This is further addressed in Holthe et al 2020 [ 36 ].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Technology can have a profound influence on how people engage in occupations and their social environment; although sometimes keeping up with changes in technology can be a challenge. Holthe et al (2020), however, found the opposite. These researchers employed a critical occupational perspective on assisted living older adults' user engagement in technology research.…”
mentioning
confidence: 91%